Sustainable Utilisation of Electric Vehicles as a Strategy to Reduce Carbon Emissions - Taglibi, Hannan Ghasan; Brilianti, Dani Fitria (Kirana Publisher (KNPub), 2024)
The transition to the use of electric vehicles in Indonesia is underway, in order to reduce the adverse climate. Transport plays an important role in the process of human life, distributing goods and services through conventional vehicles. Conventional vehicles have different fuels from electric vehicles. Reducing carbon emissions through the use of electric vehicles is a top priority to protect the climate. Electric vehicles are currently in the development process to improve energy security which is a special solution to achieve clean and environmentally friendly energy. This research aims to find out how the strategy of using electric vehicles to reduce carbon emissions and improve environmental sustainability. Electric vehicles are proving to be the ultimate solution to achieving a green economy that is more impactful for society as it completely minimizes the output of carbon gas that can damage the environment. The method used in this research is descriptive qualitative and descriptive quantitative method, and the data collection technique uses literature study. In quantitative data collection techniques, the author uses a questionnaire as a parameter to analyze the importance of using electric vehicles to achieve a green economy. The results showed that using electric vehicles can use carbon emissions and can be used as the main solution to replace conventional transport